Tinjauan Ekklesiologis atas Karya-Karya Karitatif Propria Tarekat MSC Demi Pengembangan Kemanusiaan di Merauke - Roberto U. Wirem; Gregorius Hertanto Dwi Wibowo (Jurnal Seri Mitra (Refleksi Ilmiah Pastoral), 2026)
This article offers an ecclesiological analysis of the charitable and developmental works of the Missionaries of the Sacred Heart of Jesus (MSC) in Merauke, South Papua, with particular attention to the fields of education, health, and social welfare. As a mission territory since the arrival of the first MSC missionaries in 1904, Merauke represents a complex socio-cultural and religious context shaped by border dynamics and indigenous traditions. Employing a descriptive-analytical qualitative method based on literature review and interviews with missionaries in the Archdiocese of Merauke, this study evaluates MSC initiatives in light of the Second Vatican Council’s ecclesiological vision, especially as articulated in Ad Gentes, Lumen Gentium, and Gaudium et Spes. The analysis demonstrates that MSC charitable works are not merely social services but concrete expressions of the Church’s participation in the missio Dei, promoting integral human development, affirming human dignity, and fostering social transformation. Through these ministries, the Church manifests itself as the People of God and as a sacrament of salvation within the local Papuan context.